(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
This article investigates the role and the importance of using idiomatic expressions in English language. Idiomatic expressions are group of words with concrete meaning which can be unrelated to the meaning of individual words. They make our speech more sensitive and colourful. In fact, the structure of idioms can be wrong grammatically, but the precise meaning can be seen in this way. Moreover, it can be seen that learners compare the English idiomatic expression in equivalence Russian one(in mother tongue).